Evaluasi Tingkat Pengetahuan Masyarakat tentang penggunaan Multivitamin pada Masa Pandemi Covid-19 di Apotek Izi Kabupaten Sidenreng Rappang - Linda Wilo; Fitriana Bunyanis (Universitas STRADA Indonesia, 2020)
This study aims to determine the level of public knowledge about multivitamins during the COVID-19 pandemic and the use of multivitamins during the COVID-19 pandemic at Izi Pharmacy, Sidrap Regency. The results of this study are that the level of public knowledge and the use of multivitamins during the covid-19 pandemic at IZI Pharmacy, Sidenreng Rappang Regency, that people do not know what multivitamins are and their use is also poorly understood.